Non-ohmic Mott conductivity and thermometric characteristics of heavily doped silicon structures - Shwarts, Yu.M.; Kondrachuk, A.V.; Shwarts, M.M.; Shpinar, L.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We investigated I-V curves and thermometric characteristics of heavily doped p-silicon structures at liquid helium temperatures. The variable-range hopping conductivity is shown to occur in the structures studied. The obtained parameters of non-ohmic Mott conductivity and their temperature and electric field dependencies enabled us to explain the features in structure thermometric characteristics. It is shown that both height and position of the responsivity peak depend on the extent to which the hopping conductivity is non-ohmic. They are essentially determined by the density of states near the Fermi level.